Basic motor-fitness acquisition: how are Brazilian and Portuguese children? - Luiz Antonio Pereira da Silva; Angela Maria Serápioda Silva; Marsal Pereira da Silva; Josiane Angelotti; Célia Maria Miranda; Vera Regina Ferreira Alvim (Revista da Educação Física)
Considering the child motor-development phases and the consequent genetic and sociocultural interference, and taking into account that a great majprity of Brazilian population is of Portuguese extraction, an expectation to compare Brasilian and Portuguese children’s motor development was created. To carry out the investigation 58 Portuguese elementary school children from Gondomar, in the northern area of the country, and 64 Brazilian elementary school children from Maringá, in the northern area of the State of Paraná, were chosen as samples. An eight-test battery of test was selected from AAPHERD (1980) and EUROFIT (1988). This tests were applied to all children under the same existing circumstances and by the same researcher at the beginning and at the end of the schoolyear. The analysis of the results showed that in the comparison between the two groups and regardless of gender three tests out of eight presented significant diferences (p > 0.01) in benefit of Brasilian children and only one in benefit of Portuguese children. In the post-test the Portuguese children showed a better performance decreasing the difference between the two groups when Brazilian children displayed significant favorable results in two tests against two significant favorable results of the Portuguese children. Taking into account the shortcomings and gender conditions of the two groups Silva (1995), the results suggest that Brazilian children from Maringá reach the fourth grade in better motor-fitness conditions than Portuguese children from Gondomar. However the scientifically structured and systematic work has made Portuguese schoolchildren eventually reach a better performance.